(untitled) (Perner’s Contacts, 2006)
This paper deals with problematic of implementation of flexible public transport service in low demand areas. In spite of many advantage, it is not such of type of public transport service implemented, even if the real reasons in operational and economical sense exist. In addition, the paper demonstrates these arguments on chosen PT lines.